AKTUALISASI KARAKTER KEWIRAUSAHAAN KEPALA PAUD MENUJU KETAHANAN LEMBAGA PAUD PASCA PANDEMIC COVID 19 - Wiyani, Novan Ardy (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2022)
This paper examines the actualization of the entrepreneurship character of the PAUD headmaster in order to maintain the existence of PAUD institutions in the post covid 19 pandemic, where it is known that for more than two years covid 19 has threatened the existence of PAUD institutions. The purpose of this article is to provide a description to the headmaster of PAUD both in the Playgroup, Kindergarten and Raudhatul Athfal about the various efforts that can be made to maintain the existence of PAUD institutions during the post covid 19 pandemic through actualization of the entrepreneurship character of the head of PAUD. This research is a type of library research, where data is collected using documentation techniques. The data that has been collected is then analyzed using content analysis techniques. The results showed that there are six entrepreneurial characters that can be actualized by the PAUD headmaster, including self-confidence, productivity-oriented, leadership, originality, future-oriented and honest and diligent. With the actualization of the six entrepreneurship characters of the PAUD headmaster above, it is hoped that the existence of PAUD institutions in the post-covid-19 pandemic can be maintained.